2008
DOI: 10.1016/j.dci.2007.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Low viral loads and lymphoid organ spheroids are associated with yellow head virus (YHV) tolerance in whiteleg shrimp Penaeus vannamei

Abstract: Yellow head virus (YHV) is an invertebrate nidovirus that has caused mass mortality in penaeid shrimp since 1990. Several YHV types are known, but only the original type (YHV-type 1 or YHV-1) is highly virulent. Most studies have focused on acute YHV-1 infections and there is limited work on YHV-1 survivors. We compared moribund and surviving (14%) whiteleg shrimp Penaeus (Litopenaeus) vannamei from an experimental challenge with YHV-1. Although grossly normal, all survivors were positive for YHV-1 by specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 49 publications
(82 reference statements)
2
17
0
Order By: Relevance
“…These shrimp become infected, but the level of viral propagation is reduced when compared to unselected shrimp 34 . A similar result has been reported for P. vannamei survivors from a challenge with yellow head virus 35 . Again, the mechanisms underlying the low level of viral propagation are currently unknown, but it is possible that Se may serve as an important cofactor required by the animal to respond optimally to infection.…”
Section: Resultssupporting
confidence: 88%
“…These shrimp become infected, but the level of viral propagation is reduced when compared to unselected shrimp 34 . A similar result has been reported for P. vannamei survivors from a challenge with yellow head virus 35 . Again, the mechanisms underlying the low level of viral propagation are currently unknown, but it is possible that Se may serve as an important cofactor required by the animal to respond optimally to infection.…”
Section: Resultssupporting
confidence: 88%
“…In contrast, using the same method (TEM), the presence of virions was illustrated within the spheroids but not in normal tubules [31,33]. Similarly, viral proteins were only found within the spheroid cells dsRNA-Togaviridae lymphoid organ vacuolization virus (LOVV) P. vannamei [33] by immunohistochemistry [36] and viral nucleic acid by in situ hybridization [53]. Other investigations found that ISH positive signal was detected both in normal lymphoid tubules and LOS cells [26,54] The variability in localisation of viral components within the lymphoid organ may be a sign of viral infection stages.…”
Section: Diseases Related To the Lymphoid Organ Spheroid Cellsmentioning
confidence: 96%
“…The spheroid formation might be related to the tolerance of penaeid prawn to viral infection. In the case of a survivor or in chronic infection, the spheroids were formed when animals controlled the infectious agents or at least reacted to them [36,37].…”
Section: Diseases Related To the Lymphoid Organ Spheroid Cellsmentioning
confidence: 99%
See 2 more Smart Citations